Short Communication: The relationship between content of particular metabolites of fallen mangrove leaves and the rate at which the leaves decompose over time - DAFIT ARIYANTO; DIETRIECH G. BENGEN; TRI PRARTONO; YUSLI WARDIATNO (Biodiversitas Journal of Biological Diversity, 2018)
Ariyanto D, Bengen DG, Prartono T, Wardiatno Y. 2018. Short Communication: The relationship between content of particular metabolites of fallen mangrove leaves and the rate at which the leaves decompose over time. Biodiversitas 19: 780-785. Fallen mangrove leaves contain metabolites that play a role in their decomposition in coastal conditions. This research was conducted from September 2016 to February 2017 in Pasar Banggi, Rembang, Central Java, with the purpose of investigating the impact of the leaf metabolites of various mangrove species on the rate of decomposition of the leaves in exposed litter bags The results suggested that secondary metabolites are closely involved in the decomposition of the mangrove leaves. The fastest rate of decomposition was found in Avicennia marina, and the slowest in Rhizophora stylosa. The leaves of A. marina required 10 days (half-life, t50) to decompose by 50% and this was closely related to the phosphorus content of the leaves. On the other hand, R. stylosa required 24 days (half-life, t50) to decompose by 50%.